Comparative Diagnostic of Cervical Tuberculous Lymphadenitis: PCR is a Fast, Efficient, and Improved Diagnostic Approach - Himanshu Jha; Chandra Prakash Baveja; Vinay Kamal; Prem Narayan Agarwal; Sonal Saxena; Megh Singh Dhakad; Divakar Sharma (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background and Objectives. Tuberculosis has become a major health problem in India, and the incidence of tuberculous lymphadenitis (TBLN) has increased in parallel with the increase in the incidence of mycobacterial infection worldwide. Therefore, the main objective of this study was to correlate the diagnostic efficacy of polymerase chain reaction (PCR) with various diagnostic techniques in clinically suspected cases of TBLN. Methods. The study included 100 clinically suspected cases of TBLN. Fine needle aspirate (FNA) samples were processed for cytology staining and cultured on LJ & BACTEC 12B media. The biochemical tests were performed to identify the isolates at the species level. Additionally, for PCR, DNA was extracted and used for the diagnosis and identification of mycobacterial species. Results. Patients ranged from 2 to 45 years with a mean age of 24.96 ± 9.10 years. Out of 100 patients, 73% had clinical symptoms of weight loss, followed by fever (72%), anorexia (66%), and night sweats (58%). 24% of patients were found to be smear-positive after Ziehl–Neelsen (ZN) staining and statistically highly significant with PCR. On LJ medium 34% and on BACTEC radiometric 45% of samples were smearing positive. Overall, 48% of cases were PCR-positive for TBLN. When compared with culture, the sensitivity and specificity of PCR were 93.75% and 100%, respectively, which are higher than cytology. The true positive predictive value (PPV) and negative predictive value (NPV) were 83.3% and 61.5%, respectively. Conclusion. This study suggests that PCR is a rapid, sensitive, and specific tool for correct diagnosis of TBLN cases as compared to staining and culture which lead to the early and proper management of mycobacterial diseases.